Undeath in Paradise: The Humanity of the Zombie in (Religious) Utopias - Madelon Hoedt ([sic])
The words ‘utopia’ and ‘zombie’ are likely to conjure up strong images in the mind of the reader. The first makes one think of perfection, of happiness, of something new and better; the other, of the monstrous, of death and decay. Despite the fact that these images are arguably the most common, one can question their validity: can it be said that utopias are always perfect, and are the undead always monstrous? In this paper, I aim to explore the concepts relating to both utopias and zombies and the possible connections between the two, including a reading of the undead in light of the ultimate utopia: Paradise. In the light of these analyses, I propose a more positive approach to the figure of the zombie, which will be discussed as a counterpoint to the commonly held views of (religious) utopias. Keywords: utopia, dystopia, Christianity, Revelation, Paradise, Second Coming, zombie, post-zombieA man, dressed in an old, torn and dusty suit, is seen in the distance, staggering between the tombstones as he makes his way towards the two young people, who have come to the cemetery to visit their father’s grave. They notice the man, but make fun of him; to them, the figure is not dangerous. Until he attacks them. Part of the opening sequence of George A. Romero’s Night of the Living Dead (1968), it was in this film that audiences were introduced to the now iconic figure of the shambling, flesh-eating undead. Cinemagoers saw the dead come back to life, crawling out of the earth as if it were Judgement Day. These creatures may have looked human, but were unmistakably evil, attacking and feeding on anything they could find. This negative image of the zombie existed in horror media before Romero’s reinvention of the narrative in the shape of the voodoo zombi of Haitian origins, and this vision has persisted ever since. The undead are the monstrous Other and perhaps the ultimate threat to humanity: as their numbers grow, they replace and incorporate humankind as new people are added to the ranks of the zombie. These beings may appear human, but they are dangerous and should be avoided at all cost. It seems indeed easy to apply a reading to this monster that shows them in a negative light and although the number of interpretations of the undead has grown over the years, the concept of the Other, of a being that has lost itself and is only capable of mindless feeding, has persisted. What I aim to offer here are some ideas on different interpretations of the undead, most notably a more positive reading. Film makers and academics alike have almost universally presented the zombie as a monstrous Other, something which should be avoided and killed. Any relation to the perfection of a (religious) utopia would therefore appear impossible, yet it is the potential of the undead to be seen as more than brainless monstrosities that I wish to address here. What I would like to put forward is a more positive approach to the figure of the zombie, ultimately arguing that the undead may be the only way in which humanity can achieve Paradise. In order to facilitate such a discussion, I will start by examining the terminology used. Reference has already been made to images of perfection and monstrosity, respectively, and it will be beneficial to explore the concept of both utopia and the zombie in more detail, before moving on to a discussion of the idea of the perfect undead.